Mechanical test relevance—A personal perspective on some methods and requirements - Darvell, Brian W. (Frontiers in Dental Medicine, 2023)
Mechanical tests of various kinds are widely used in dental research to study the behaviour of its materials. Unfortunately, despite its often long history, the relevance of a test or its outcome is hard to discern. But even for tests that have a more apparent appropriateness, many details that ensure good accuracy and reproducibility appear not to be appreciated or understood in that there is little evidence in the published literature that the necessary steps and precautions have been taken. The present purpose is to examine a number of these aspects in the context of a selection of tests to illustrate the care and attention that are essential for sound results.